Pithouses versus pits : apuntes para la resoluciónde un problema arqueológico - Jiménez Jáimez, Victor (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
In this article, we try to facilitate the solution of archaeological problems concerning the identification of semi-subterranean houses and propose some key points to distinguish them from other types of pits. In first place, we present a brief history of the concept of dwellingpit. In second place, we describe the main data currently known about houses in pits from archaeology, ethnography and experimental archaeology. Finally, some reflections are made on the characteristic properties of these issues in order to improve our ability to recognise them archaeologically.